Kepuasan Pelanggan Bakso: Peran Kualitas Pelayanan, Persepsi Harga, dan Kualitas Produk - Andre Rodin Herianto (Oikonomia: Jurnal Manajemen, 2023)
Purpose Service quality is essential for a service business. Meatball outlets are services including products, so this study aims to analyze the influence of service quality, price perceptions and product quality on customer satisfaction of Bakso Malang Karapitan D'mall Depok. Methodology The population in this study were all customers of Bakso Malang Karapitan D'mall Depok. The population is uncertain and difficult to estimate, so the sample size is based on expert policy, and is set at 100 respondents. The selection of 100 respondents was carried out by incidental sampling. Then the data were analyzed using multiple regression techniques with the SPSS 26 tool. Findings The proven results are supported by data that customers of Bakso Malang Karapitan D'mall Depok are increasingly satisfied when the quality of service and products is further improved, and prices are perceived to be more in line with expectations. Suggestion need to increase the durability of the meatballs more durable, and also be careful in setting prices to be able to match the expectations perceived by customers.